Evaluation of the relationships between corneal parameters, ocular biometry, and myopia magnitude - Mohd Izzuddin Hairol; Norlaili Arif; Yong, Pui Theng; Mariah Asem Shehadeh Saleh Ali; Nik Nor Adlina Nik Idris; Ng, Li Ching (Penerbit Universiti Kebangsaan Malaysia, 2021)
Axial length of the eye correlates with the magnitude of myopia. However, there are conflicting reports on the relationship between certain corneal parameters with myopia magnitude. The objective of this study was to compare ocular biometry and corneal parameters between emmetropic and myopic groups. Participants (n=127) were categorized as emmetropia (spherical equivalent, SE, ±0.50D), low myopia (-0.75D≤SE<-6.00D) and high myopia (SE≥-6.00D). The difference in axial length, anterior chamber depth, and vitreous chamber depth between emmetrope, low myope, and high myope were highly significant (one-way ANOVA, all p<0.001) with significant correlations between SE and all these parameters (simple regressions, all p<0.001). However, central corneal thickness, corneal radius of curvature, and corneal asphericity between these groups, and the correlations between the ocular parameters with SE were not significantly different (all p>0.05). Corneal curvature correlated significantly with axial length (p=0.001) but not with myopia magnitude (p=0.91). Rather than myopia magnitude, axial length appears to be more sensitive to detect changes in corneal curvature in myopes. In conclusion, myopic patients’ axial length should be carefully considered for interventions that involve the cornea, such as orthokeratology and refractive surgery.